A Quranic View on The Belief-Oriented Standard of Human Ethics - Zamakhsyari bin Hasballah Thaib; Mukhamad Hadi Musolin; Vina Annisa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the Qur’anic foundations of moral standards by examining the relationship between belief (ʿaqīdah) and morality as reflected in selected Qur’anic verses. Employing a thematic interpretation (tafsīr maudhū‘ī) through a descriptive-analytical method and inductive reasoning (istiqrā’), this research investigates how ethical conduct is shaped within the Qur'anic worldview. The key finding highlights that, according to the Qur’an, morality is inherently practical and action-oriented. It emphasizes the necessity of righteous deeds as a pathway to human nobility and true happiness. Moral obligations, in this context, are not abstract theories open to speculation, but imperatives that demand immediate implementation. The Qur’an positions revelation—not reason or custom—as the ultimate source of moral authority. Furthermore, the Qur’anic standard of ethical belief is deeply rooted in core theological principles such as tawḥīd (divine oneness), trust in God, sincere intention, and love, which collectively guide the moral conscience of a believer.